Escrever a morte para sobreviver : uma literatura suicida em Sérgio Sant’Anna - Rodrigues, Danielle Santos (2022)
This thesis analyses the short story production of the writer Sérgio Sant’anna, in particular, the narratives in which suicide is present. This theme is constantly addressed in the work of this author, which is in itself extensive. In our readings, in 11 short story books, published between 1973 and 2017, we listed a total of 38 short stories that deal with suicide, directly or indirectly, presenting it in different ways, as an element of narrative effect. We work on the idea that the self-inflicted death, because it is a mystery, a taboo, has a narrative-generating force. Thus, it is through suicide that many short stories of the author are born, that they become alive and impactful. In this sense, in a specific way, we explore the link between suicide, survival and salvation. In some of the short stories, there are characters-writers distressed before the impossibility of writing, they write to survive, to save themselves from suicide or to save themselves by means of suicide. So, it is writing about killing himself, that the writer escapes the death announced by the fearsome blank page. To analyze this aspect, we draw on Todorov (2011), Agamben (2018), Freud (1996), Carvalho (2003), and Duras (1994). Similarly, in the wake of self-fiction, Sérgio Sant’anna himself writes death to survive, as it can be seen in the short story “A barca da noite” (2003), in which he narrates his own suicide attempt. We make this argument based on Arfuch (2012), Bakhtin (2011), Klinger (2006), Prelorentzou (2017), Orthof (1996) and Sibilia (2015). We also analyze how Sant’Anna’s writing on suicide is indicative of a literature that survives after successive crises of demystification (SONTAG, 2015). To do so, we draw on Adorno (1970); Sontag (1967), Han (2019) e Murdoch (1972). Finally, we examine the writing undertaken by Sant’Anna, observing suicide as an indication of antinarrative, as a matter and technique that the author uses to conceive his texts. The execution of our study is based on methodological resources related to bibliographic research. We make predominant use of concepts from the areas of Literary theory and Comparative Literature, Philosophy and cultural theories, given the transdisciplinary character of our theme. The approach is qualitative and established by a critical-analytical and interpretative study.